2013
DOI: 10.3389/fnsys.2013.00123
|View full text |Cite
|
Sign up to set email alerts
|

Developmental plasticity of spatial hearing following asymmetric hearing loss: context-dependent cue integration and its clinical implications

Abstract: Under normal hearing conditions, comparisons of the sounds reaching each ear are critical for accurate sound localization. Asymmetric hearing loss should therefore degrade spatial hearing and has become an important experimental tool for probing the plasticity of the auditory system, both during development and adulthood. In clinical populations, hearing loss affecting one ear more than the other is commonly associated with otitis media with effusion, a disorder experienced by approximately 80% of children bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 196 publications
(356 reference statements)
3
80
0
1
Order By: Relevance
“…However, it is important to note that from the 6 patients with > 10 years of deafness of duration, 4 lost their hearing after age of 12. Normal binaural hearing during the development of bilateral auditory pathways may explain why these patients had an improvement in spatial hearing even after a prolonged period of hearing deprivation (Grothe et al 2010;Litovsky et al 2010;Keating & King 2013). Electrophysiological studies have demonstrated that if unilateral deafness occurs after maturation of bilateral pathways the lateralization of contralateral activation of the auditory areas is not altered (Langers et al 2005) supporting the idea that localization may be improved even if cochlear implantation occur after a longterm unilateral deafness.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, it is important to note that from the 6 patients with > 10 years of deafness of duration, 4 lost their hearing after age of 12. Normal binaural hearing during the development of bilateral auditory pathways may explain why these patients had an improvement in spatial hearing even after a prolonged period of hearing deprivation (Grothe et al 2010;Litovsky et al 2010;Keating & King 2013). Electrophysiological studies have demonstrated that if unilateral deafness occurs after maturation of bilateral pathways the lateralization of contralateral activation of the auditory areas is not altered (Langers et al 2005) supporting the idea that localization may be improved even if cochlear implantation occur after a longterm unilateral deafness.…”
Section: Discussionmentioning
confidence: 92%
“…In the last few years, human and animal studies have demonstrated that there is a critical period for bilateral auditory pathway development explained by neuronal reorganization of the auditory brain following prolonged monaural hearing input in bilateral congenital profound deafness (e.g., Gordon et al 2011Gordon et al , 2013Kral et al 2013). Keating and King (2013) also suggested that spatial hearing might be affected permanently if an extended period of asymmetrical hearing input occurs at a young age. Age of onset of deafness was not analyzed in this study due to small sample size.…”
Section: Discussionmentioning
confidence: 98%
“…The non-human studies that have explored the effects of CHL on auditory perception primarily focus on the impact of unilateral hearing loss on sound localization, and neural encoding properties that support binaural processing (Clements et al, 1978; Keating et al, 2013a; Keating et al, 2013b; Kelly et al, 1987; Knudsen et al, 1984a; Knudsen et al, 1984b; Moore et al, 1999). However, since otitis media with effusion is more commonly bilateral in humans (Engel et al, 1999), it is important to study the consequences of mild to moderate binaural hearing loss on the perception of spectral or temporal cues that support speech comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three aforementioned benefits, only the head shadow effect does not rely upon fused information, while the binaural summation and binaural squelch effects require it. Furthermore, after years of having to process asymmetric inputs, the neural circuitry may have been affected by plasticity so that time and training may be needed before binaural advantages recover [Keating and King, 2013].…”
Section: Robustness Of Binaural Benefits In Cases Of Asymmetric Rehabmentioning
confidence: 99%
“…If the two ears process sound in such a way that interaural differences are accurately encoded in 4 episodes of unilateral conductive hearing loss, trigger plastic changes in neuronal wiring and in brain processing, with these changes being more intense during some critical periods. The purported amblyaudia [Keating and King, 2013], as referenced to amblyopia in the visual world, is the most extreme consequence, and the reversibility of this plasticity is an important matter of concern. There would be no sense in trying to rehabilitate the poorer ear of an amblyaudic patient by just sending crude and distorted cues into non-existing circuits.…”
Section: Introductionmentioning
confidence: 99%